Inter-kingdom communication and the sympoietic way of life - Gilbert, Scott F. (Frontiers in Cell and Developmental Biology, 2024)
Organisms are now seen as holobionts, consortia of several species that interact metabolically such that they sustain and scaffold each other’s existence and propagation. Sympoiesis, the development of the symbiotic relationships that form holobionts, is critical for our understanding the origins and maintenance of biodiversity. Rather than being the read-out of a single genome, development has been found to be sympoietic, based on multigenomic interactions between zygote-derived cells and symbiotic microbes. These symbiotic and sympoietic interactions are predicated on the ability of cells from different kingdoms of life (e.g., bacteria and animals) to communicate with one another and to have their chemical signals interpreted in a manner that facilitates development. Sympoiesis, the creation of an entity by the interactions of other entities, is commonly seen in embryogenesis (e.g., the creation of lenses and retinas through the interaction of brain and epidermal compartments). In holobiont sympoiesis, interactions between partners of different domains of life interact to form organs and biofilms, wherein each of these domains acts as the environment for the other. If evolution is forged by changes in development, and if symbionts are routinely involved in our development, then changes in sympoiesis can constitute an important factor in evolution.